Identifikasi Kedalaman Dan Ketebalan Lapisan Lunak Di Area Kantor Pengawasan Keuangan Dan Pembangunan Kabupaten Mamuju Menggunakan Metode Geolistrik Resistivitas - Hasrianto Hasrianto; Raivel Raivel; Saddam Husein (Program Studi Teknik Pertambangan, Fakultas Teknik, Universitas Sulawesi Tenggara, 2026)
The Mamuju City area, West Sulawesi, was significantly impacted by the 2021 earthquake. Earthquake vibrations can be amplified if they pass through soft soil layers, potentially increasing building damage. The Mamuju City Financial and Development Supervision Office (PKP) area is a vital infrastructure that requires subsurface assessment. This study aims to identify the depth, thickness, and lateral distribution of soft layers below the surface of the Mamuju PKP Office Area. The method used is the Schlumberger configuration geoelectric resistivity with a single measurement path from the correlation of three geoelectric resistivity sounding points. Data processing was carried out with inversion software to produce a 2D subsurface resistivity model. The inversion results indicate the presence of three main layers: First Layer (Zone A): Has a resistivity of 4.09 - 64.5 Ωm with a thickness of between 5 and 36.7 meters. This layer is interpreted as weathered sandy reef limestone saturated with water through intergranular flow, with a soft/loose layer condition. This layer is the main soft layer that has the potential for amplification. Second Layer (Zone B): Has a resistivity of 0.02 – 4.09 Ωm with a thickness that varies between 11 to 22.4 meters. This layer is dominated by weathered material of sandy reef limestone or highly weathered rock. This layer is the main soft layer that has the potential for amplification. Third Layer (Zone C): Has a resistivity of 64.5 – 22048.1 Ωm. This layer is interpreted as a harder and more compact bedrock. The depth of this bedrock varies, starting from around 2 to 10.6 meters. This layer is a hard/compact layer. The conclusion is that the identified soft layer based on the resistivity geoelectric interpretation consists of 2 layer zones, namely the first layer (Zone A) and the second layer (Zone B) with a resistivity value of <64.5 Ωm, a layer thickness of 5 to 36.7 meters, a layer depth of 0 to 34.3 meters. The presence of this thick soft layer has the potential to become an earthquake amplification zone, so it needs to be taken into consideration in earthquake mitigation and engineering planning for rebuilding or retrofitting structures in the area.